Why You Don’t Have to Choose between Accuracy and Human Officiating (But You Might Want to Anyway) - S. Seth Bordner (Philosophies, 2019)
Debates about the role of technology in sports officiating assume that technology would, ceteris paribus, improve accuracy over unassisted human officiating. While this is largely true, it also presents a false dilemma: that we can have accurately officiated sports or human officials, but not both. What this alleged dilemma ignores is that the criteria by which we measure accuracy are also up for revision. We could have sports that are so defined as to be easily (or at least more accurately) judged by human officials. A case from the recent history of science provides an instructive example. I argue that if we insist on human officials, we can still aim for maximal accuracy, though there will be tradeoffs. With compelling reasons to want accuracy in officiating, however, these tradeoffs effectively serve as a reductio against the use of human officials unaided by technology.